2014
DOI: 10.1021/op500131u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ionic Liquids Equipped with 2-Methoxyethoxymethyl/Methoxymethyl Groups Using a Simple Microreactor System

Abstract: A simple microreactor system has been utilized for the continuous flow synthesis of novel ionic liquids having a (2-meth­oxy­ethoxy)methyl or methoxy­methyl substituent. Conversion rates of N-bases and tributylphosphine in the microreactor system are faster than those in the batch system because of less diffusion distance in the tube reactor. This method allows us to prepare ionic liquids in efficient yields with high purity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…NMR spectra were recorded using a 5 mm probe on a Varian Inova 400 spectrometer. Spectroscopic data of ILs 1 , 2 , 3 , and 4 were in accordance with the literature. , …”
Section: Methodssupporting
confidence: 86%
“…NMR spectra were recorded using a 5 mm probe on a Varian Inova 400 spectrometer. Spectroscopic data of ILs 1 , 2 , 3 , and 4 were in accordance with the literature. , …”
Section: Methodssupporting
confidence: 86%
“…To the best of our knowledge, although the preparation and a part of physicochemical properties of Pyr 1,6 TFSA and Pyr 1,1O2O1 TFSA have been reported, [34,35] those of Pyr 1,1O4 TFSA and Pyr 1,4O1 TFSA have not. The physicochemical properties of these four RTILs were therefore evaluated under an inert atmosphere.…”
Section: Resultsmentioning
confidence: 89%
“…Two kinds of ionic liquids used in this study were synthesized by an organic method as previously reported, 35 and are shown in Fig. 1.…”
Section: Preparation Of Electrolytes and Electrodesmentioning
confidence: 99%